Comparison of audio and audiovisual measures of adult stuttering: Implications for clinical trials. (2nd November 2015) - O'Brian, Sue; Jones, Mark; Onslow, Mark; Packman, Ann; Menzies, Ross; Lowe, Robyn
Abstract: Purpose : This study investigated whether measures of percentage syllables stuttered (%SS) and stuttering severity ratings with a 9-point scale differ when made from audiovisual compared with audio-only recordings. Method : Four experienced speech-language pathologists measured %SS and assigned stuttering severity ratings to 10-minute audiovisual and audio-only recordings of 36 adults. Result : There was a mean 18% increase in %SS scores when samples were presented in audiovisual compared with audio-only mode. This result was consistent across both higher and lower %SS scores and was found to be directly attributable to counts of stuttered syllables rather than the total number of syllables. There was no significant difference between stuttering severity ratings made from the two modes. Conclusion : In clinical trials research, when using %SS as the primary outcome measure, audiovisual samples would be preferred as long as clear, good quality, front-on images can be easily captured. Alternatively, stuttering severity ratings may be a more valid measure to use as they correlate well with %SS and values are not influenced by the presentation mode.